NGS amplification panel for HBV (Hepadnaviridae: Orthohepadnavirus) sequencing - Mikhail D. Chanyshev; Natalia V. Vlasenko; German V. Roev; Ivan A. Kotov; Albina G. Glushchenko; Vera V. Makashova; Kamil F. Khafizov; Vasily G. Akimkin (Вопросы вирусологии, 2024)
Introduction. Hepatitis B virus (HBV) remains a pressing global public health concern. The clinical course of the disease, particularly its tendency towards chronicity and response to therapy, is significantly influenced by the HBV genotype and specific mutations. There is an imperative need for a straightforward, highly sensitive, and dependable method for whole genome sequencing of HBV.